INNOVATIVE DEVELOPMENT OF THE MODERN PHYSICAL EDUCATION SYSTEM AND ITS IMPACT ON A HEALTHY LIFESTYLE (American Journal of Technology and Applied Sciences, 2025)
This article presents a scientific analysis of the innovative approaches to developing the modern physical education system and their proven impact on public health and the formation of a healthy lifestyle. The research is grounded in statistical data from Uzbekistan and international sources, advanced technological solutions, and empirical observations in the fields of education and sports. The effectiveness of physical education processes—such as the integration of mobile applications, interactive methods, digitalization of sports infrastructure, assessment of youth and adult health, and the implementation of innovative projects in primary and higher education—has been scientifically substantiated. The real impact of physical education on economic, sociological, and medical indicators is described using statistical and analytical methods. The results demonstrate the potential for wide-scale adoption of a healthy lifestyle philosophy, increasing physical activity rates, reducing healthcare expenditures, and enhancing overall social well-being.